2019
DOI: 10.1186/s42234-019-0035-x
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective trial examining safety and efficacy of microcurrent stimulation for the treatment of sinus pain and congestion

Abstract: Background: Inflammation and swelling of the sinus and nasal mucosa are commonly caused by viral infection, bacterial infection, or exposure to allergens and irritants. Sinonasal inflammation can cause symptoms of nasal congestion, facial pressure, and rhinogenic facial pain or "sinus pain". A previous randomized controlled study demonstrated that acute treatment with non-invasive periorbital microcurrent stimulation resulted in a rapid and clinically meaningful reduction in self-report of sinus pain that sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The copyright holder for this preprint this version posted April 15, 2024. ; https://doi.org/10.1101/2024.04. 10.24305618 doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted April 15, 2024. ; https://doi.org/10.1101/2024.04. 10.24305618 doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…As there was no motivation for device manufacturers to develop proper clinical utility and generate high quality efficacy data, clinical evidence has continued to be debated [3,4]. Newer indications such as TENS for migraine and sinus pain have however demonstrated definitive clinical utility [9][10][11]. TENS devices are considered medium risk (Class 2) devices and are available for both prescription and OTC use.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no serious adverse events requiring medical treatment were reported. In a trial examining the safety and efficacy of MCT for sinus pain and congestion, it was concluded that MCT is safe with only minor side effects (tingling in the feet), which were resolved without medical intervention (Goldsobel et al 2019 ). MCT has been applied in many medical scenarios, being reported as a safe therapy over the decades (Al-Tubaikh 2018 ; Xu et al 2021 ).…”
Section: Side Effects Of Using Microcurrent In Healthy Humansmentioning
confidence: 99%
“…Microcurrent therapy has an unrealised potential in healing dysfunctional tissue because of its ability to mimic weak, natural bioelectric ‘injury currents’, and subsequently enhance wound repairing (Poltawski and Watson 2009 ). In addition, within the clinical setting MCT has been widely applied in patients to reduce and relieve sinus pain (Goldsobel et al 2019 ; Maul et al 2019 ), chronic scar pain and itch from skin scars (Perry et al 2010 ; Ud-Din et al 2013 ), chronic back pain (Lerner and Kirsch 1981 ), and partial rotator cuff tears related pain (Vrouva et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microcurrents below 100 µA are harmless to the human body [22,23]. PB has been approved by the FDA, US Federal Communications Commission, Korea Certification mark (Korea), Conformite European mark (Europe), Product Safety Electrical mark (Japan) as safe.…”
Section: Safety Assessmentmentioning
confidence: 99%